2021
DOI: 10.1016/j.stemcr.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Ablating Adult Neural Stem Cells Improves Synaptic and Cognitive Functions in Alzheimer Models

Abstract: Summary Adult neurogenesis is impaired in the hippocampus of patients with Alzheimer disease (AD) as well as AD models. However, it is far from clear how modulating adult neurogenesis affects AD neuropathology. We confirm that adult hippocampal neurogenesis is impaired in two AD models. Surprisingly, however, cognitive functions are improved in AD models after ablating adult neural stem cells (aNSCs). Ablation of aNSCs does not affect the levels of amyloid β but restores the normal synaptic transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 59 publications
4
26
2
Order By: Relevance
“…Recently, we examined the effects of inhibiting AHN on synaptic and cognitive functions in AD mice by using two AD models with two approaches to inhibit AHN. Our data suggest that inhibiting AHN improved synaptic and cognitive functions in AD mice (Zhang et al, 2021). In a previous study, Hollands et al reported that depletion of adult neurogenesis exacerbates cognitive deficits in AD by compromising hippocampal inhibition (Hollands et al, 2017).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Recently, we examined the effects of inhibiting AHN on synaptic and cognitive functions in AD mice by using two AD models with two approaches to inhibit AHN. Our data suggest that inhibiting AHN improved synaptic and cognitive functions in AD mice (Zhang et al, 2021). In a previous study, Hollands et al reported that depletion of adult neurogenesis exacerbates cognitive deficits in AD by compromising hippocampal inhibition (Hollands et al, 2017).…”
supporting
confidence: 58%
“…This concern is actually another reason why we tried to evaluate the effects of inhibiting AHN on pathology and memory of AD mice in different models, and with different approaches. As shown in Figure 7I in our paper ( Zhang et al., 2021 ), deleting AHN with GFAP-TK/GCV improved memory in hAPP-J20 mice as well, and there was only a short period of time following the GCV treatment before behavioral tests. This effect was also in line with the results of MAM treatment in hAPP-J20 mice as shown in Figure 3 in our paper.…”
Section: Main Textmentioning
confidence: 50%
See 1 more Smart Citation
“…Brain sections were incubated with mouse anti‐parvalbumin antibody (1:2000, Swant, Marly, Switzerland) followed by incubation with the corresponding anti‐mouse antibody conjugated to FITC (1:250, Vector Laboratories). Quantifications were as described previously with modifications (Francis, 2003; Pan et al, 2016; Zhang et al, 2018; Zhang et al, 2021). PV + cells in the hippocampus and DG were counted by collecting four matched sections spanning the bregma (−1.46 and −3.16 mm) with a 40× objective lens on a fluorescent microscope (Olympus BX53).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a recent study by Zhang et al. suggests that ablating neurogenesis improves synaptic and cognitive function in FAD mice ( Zhang et al., 2021 ). Upon closer examination of the experimental approach, we raise questions concerning the study design and the authors’ interpretation of the results, and thus, reveal critical differences between this study and the existing body of literature (see for example [ Choi et al., 2018 ; Hollands et al., 2017 ]).…”
Section: Main Textmentioning
confidence: 91%